Rancang Bangun Sistem Informasi Berbasis Web untuk Mengevaluasi Indeks Keandalan Loss of Load Probability (LOLP) Pembangkit Listrik - Naradhiya, Gede; Jasa, Lie; Wiharta, Dewa Made (Jurnal Teknik Industri Terintegrasi (JUTIN), 2025)
Electrical energy is a vital need that continues to increase every year, thus the reliability of its supply needs to be monitored so that electricity distribution is in accordance with the established standards. The calculation of the reliability of power plants in supplying electricity is called the reliability index. This study aims to evaluate the reliability index of power plants using a web-based information system designed and built by the author. The evaluation of the reliability index was carried out using the LOLP (Loss of Load Probability) method based on the PLN 2016-2025 RUPTL standard. The accuracy of the information system performance was assessed using the MAPE (Mean Absolute Percentage Error) method by comparing the results of the information system calculations to three reference studies. The calculation results showed a MAPE value of the information system of 2.4233%, which is classified as "Excellent" in the MAPE results classification.